2013
DOI: 10.1155/2013/860431
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Confluence Flow in Open Channel with Dynamic Meshes Techniques

Abstract: Due to the interaction between branch flow and main stream at confluence zone in open channel, the water level of free surface often varies dramatically. In three dimensional simulations of confluence flow, multi-phase models are usually adopted in treating the free-surface boundary, for example, the Volume of Fluid model. The major dilemma for adopting multi-phase modes is that the method consumes more time and computation resources. In this study, the new mesh technique, the dynamic meshes, is adopted to tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The same model and experimental test were used by Djordjevic [12] to study the effects of upstream planform curvature and bed elevation discordance between the tributary and main channels on the confluence hydrodynamics. However, Yang et al [31], by using the commercial software FLUENT (ANSYS Inc., Canonsburg, PA, USA) and, again, the data of Shumate [18], showed how the adoption of dynamic meshes could give much higher accuracy than that of Volume of Fluid (VoF) or rigid lid method. The experimental tests of Birjukova et al [23] were reproduced by Brito et al [32], comparing the results obtained with different turbulence closure models for solving the RANS equations.…”
Section: Introductionmentioning
confidence: 99%
“…The same model and experimental test were used by Djordjevic [12] to study the effects of upstream planform curvature and bed elevation discordance between the tributary and main channels on the confluence hydrodynamics. However, Yang et al [31], by using the commercial software FLUENT (ANSYS Inc., Canonsburg, PA, USA) and, again, the data of Shumate [18], showed how the adoption of dynamic meshes could give much higher accuracy than that of Volume of Fluid (VoF) or rigid lid method. The experimental tests of Birjukova et al [23] were reproduced by Brito et al [32], comparing the results obtained with different turbulence closure models for solving the RANS equations.…”
Section: Introductionmentioning
confidence: 99%
“…When two channel flows meet at the confluence, due to the difference in velocity field in main and tributary channels, there is usually a shear plane existing between them, which is recognized as the major source of turbulence generation. 10 With the stagnation zone as the beginning of the shear plane, a separation zone is usually generated downstream of the branch channel and marked as the source of turbulence. In the separation zone, velocity magnitude is often small, while the velocity gradient near the edge of the separation zone is large.…”
Section: Effects Of Confluence Anglementioning
confidence: 99%
“…More recently, many studies have investigated confluence flow in open channel based on energy equations, momentum equations, and potential theory with dynamic mesh techniques. [8][9][10] Beyond the morphological hydraulic research of river confluences, the consideration of sediment-flow interactions spawns a significant new phase of study. Mosley 11 introduced a flume experiment in which a mixture of sand and silt was used to study how sediment load influences the development of central scour hole at Y-shaped junctions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to govern the free surface condition, an opening boundary condition was imposed on the model. The Volume of Fluid (VOF) method was used to calculate the water level in the process of iteration (Chen, Dai, & Liu, 2002a;Chen, Chau, & Kouh, 2002b;Hirt & Nichols, 1981;Liu & García, 2008;Yang et al, 2013).…”
Section: Numerical Modelmentioning
confidence: 99%
“…Momplot et al (2012) investigated the effect of mesh refinement and various turbulence models on the performance of open-channel junction CFD modeling. Yang, Liu, Lu, and Wang (2013) indicated that the dynamic mesh technique performs better than rigid-lid and VOF in free-surface simulation. Xie, Lin, and Falconer (2013) predicted the turbulence structure of open channels using large eddy simulation and predicted the main velocity, secondary velocity, boundary shear stress and Reynolds stress.…”
Section: Introductionmentioning
confidence: 99%